Paper-work: what module guides have to say about assessment practices - Enriquez, Judith (PRISM: Casting New Light on Learning, Theory and Practice, 2020)
Documents are usually circulated as carriers of transparent information. They can serve as evidence of accountability. In fact, they embody the most desired value of managerialism, where the culture of audit and compliance is fully served and delivered in written and textual form. This article explores assessment by attending to its principal instrument – the document – through which it is organised, monitored and implemented in higher education. It is an invitation to ‘see’ what documents, such as, module guides, ‘do’ for universities and the assessment practices of academics. Under close scrutiny, documents ‘do’ more than record and transfer information. Their associated paper-work expresses and reproduces norms, patterns of thoughts and work habits that are accepted and assumed to be shared in the prevailing outcome-based assessment systems of higher education. This article provides a critical account based on practice-oriented and material-semiotic approaches to assessment. It bears witness to the past and persistent norms and standards that are shaped by documents, paper-work, control, compliance and surveillance and less by pedagogical and student engagement.